Improved Digital Image Quality Using the Gaussian Filter Method - S Sriani; Ilka Zufria; Mhd. Syahnan (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Digital imagery from digital image cameras often has some disturbances that may occur, such as lenses not focusing, spots appear caused by the imperfect capture process. This ineptness can be caused by uneven lighting resulting in uneven intensity, low image contrast and the appearance of noise in the image. Of course all these negative effects will reduce the quality on digital imagery. To overcome the noise, efforts need to be made to improve the quality of that image. One of them is by filtering the image both linearly and non-linearly. There are many methods that can be used to perform linear and non-linear filtering. Images that contain noise can limit the valuable information needed when image analysis is done. Gaussian filter is one of the linear filters that serves to smooth and eliminate noise in an image. Mean Filter is very simple and easy to implement and is very useful for reducing the variation in value of a pixel with the next pixel. This filter works by replacing the intensity of the pixel value with the average the neighboring pixels.